Legitimação das fichas perinatal e de diagnóstico de enfermagem para consulta à gestante e/ou puérpera - ALBUQUERQUE, Jaqueline Lisboa de (2019)
In the direction of the assistive technologies, it was developed a form to collect data from women in pregnancy and puerperium to facilitate the dynamics of care. To implement this work we have created a potential nursing diagnoses, subdividing the pre-natal into quarters, and puerperium. The main objective is the legitimisation of Perinatal card and nursing Diagnoses card .The Research relied on five different times. At the first moment, registered to the card in the registry of intellectual property of the UFPA; in the second, the cards were sent to four expertise, where these by analyzing the assistive technologies, gave opinions on the validity of the cards in the use of collective health; the third was the orientation to nursing students to the correct entries of the cards proposals; in the fourth moment consisted in the application and evaluation of TAs by academics from the 3rd semester and finally, in the fifth time there was the testing of the cards reworked by the researchers. Being that the last two steps were performed in the Unit of Health of the city Belém, Pará, for 22 students in 53 visits. The study this is an action research and was developed as proposed insertion of TAs in primary health care. The data were collected by means of a questionnaire and the connector of the first applied to students after the use of the second by them in the nursing appontiment. The data collected were distributed variables in spreadsheets using Microsoft Office Excel 2010 and categorized. The analysis of results, was the discussion with findings in the literature by confronting them with the categories created. According to the respondents, 100% assessed that the card Perinatally is a good instrument for data collection, 86.36% claim that it assists in; 86.36% assessed that the card nursing diagnoses helped in their assistance/conduct during the prenatal/puerperium, and 95.45% that it has some relevance to academia and/or health services. The results showed that the insertion of TAs in nursing appointment for assistance to pregnant and postpartum women had positive effects, aiding in qualifying, optimization and effectiveness of consultation; helping the students in the direction of the Systematization of Nursing Care, in the organization of the data collection and giving security in time of conduction of the nursing oppointment . Then we can conclude that the objective was reached, we managed to execute the five steps and now the connectors are validated and considers that these TAs contribute, facilitating the teaching-learning process.